2017
DOI: 10.1089/cyber.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Location and Modality Effects in Online Dating: Rich Modality Profile and Location-Based Information Cues Increase Social Presence, While Moderating the Impact of Uncertainty Reduction Strategy

Abstract: This study investigates how different interface modality features of online dating sites, such as location awareness cues and modality of profiles, affect the sense of social presence of a prospective date. We also examined how various user behaviors aimed at reducing uncertainty about online interactions affect social presence perceptions and are affected by the user interface features. Male users felt a greater sense of social presence when exposed to both location and accessibility cues (geographical proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Especially because the voice (and the person, respectively) was unknown (also without any further information one would normally get, e.g., on dating sites, such as age or hobbies), it seems plausible that the perceived connection to the computer-mediated human played an important role in the interest in further messages. This would be in line with Jung et al (2017) who found that within dating sites, social presence (enhanced by more details within the dating profile) is connected with the willingness to meet the dating partner as it is stated to reduce uncertainty. This, however, is not the case for the voice assistant, as social presence did not significantly predict the interest in further messages.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Especially because the voice (and the person, respectively) was unknown (also without any further information one would normally get, e.g., on dating sites, such as age or hobbies), it seems plausible that the perceived connection to the computer-mediated human played an important role in the interest in further messages. This would be in line with Jung et al (2017) who found that within dating sites, social presence (enhanced by more details within the dating profile) is connected with the willingness to meet the dating partner as it is stated to reduce uncertainty. This, however, is not the case for the voice assistant, as social presence did not significantly predict the interest in further messages.…”
Section: Discussionsupporting
confidence: 85%
“…This state is crucial for the participation in a sexualized interaction with an artificial entity, as it (additionally to sexual arousal) shifts the focus on sexual gratification rather than potential deviations from sexual and social norms. Social presence has also been linked to perceived attractiveness (compare e.g., Fromberger et al, 2015 ; Croes et al, 2016 ) and was shown to be related to intention to meet a dating partner when meeting on a dating website ( Jung et al, 2017 ). However, these studies have been primarily focusing on visual and informational stimuli (e.g., pictures, videos, information about geographical proximity) so far.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…confianza y compromiso influenciados por el diseño de interacción Se descubrió que la sensación de presencia humana alivia el miedo y la desconfianza y aumenta el compromiso y el deseo de interacción (Jung et al, 2017) y se puede crear a través de la interfaz de usuario, como compartir el estado, la ubicación o el objetivo (Niemantsverdriet et al, 2019). Se descubrió que la desconexión se evita proporcionando un historial de interacción a través del historial de chat (Shyam Sundar et al, 2016).…”
Section: Relationships and Healthunclassified
“…While the above articles mostly study technical advantages, location information—or more precisely proximity information—cannot only reduce costs for providers, it also makes products more attractive and can even be considered a product by itself. A study by Jung et al [ 100 ], for instance, found that proximity increases social presence for male participants in online-dating sites and resulted in increased intention to buy paid memberships. But the desire to know about the location of a potential romantic partner may be less than innocent, and women may regret that their location is monetized by the service.…”
Section: The Value Of Location Datamentioning
confidence: 99%
“…An automatic news summarization that takes location into account, e.g., to be able to warn users about emergency situations nearby was proposed by Chen [ 26 ] in 2010. Location awareness has also recently been shown to increase satisfaction in online-dating sites [ 100 ], although Abbas [ 1 ] in a study in 2011 still noted that the study participants’ willingness to share location information varied depending on the amount of trust within a relationship, as would be predicted given the value of location data. Location-based music services are the focus of Åman et al [ 6 ].…”
Section: Types Of Applicationsmentioning
confidence: 99%